INTRODUCTION - BORBELY, Carmen-Veronica (Studia Universitatis Babeș-Bolyai Philologia, 2018)
In an essay mapping the space of poetic imagination, Seamus Heaney, Irish Laureate of the 1995 Nobel Prize in Literature, reinforces the Joycean notion that the clarity of individual artistic vision may depend on one’s (self)reflexive displacement from one’s cultural roots, whose creative energies can best be tapped from a distant vantage point, situated on “the viewing deck of Europe” (Heaney 2012, 19). Echoing Stephen Dedalus’s diary notation in The Portrait of the Artist as a Young Man, which condenses the idea that Irishness is inescapably both a pole of departure and a horizon of expectation for the exilic artist, Heaney’s title – “Mossbawn via Mantua. Ireland in/and Europe: cross-currents and exchanges” – juxtaposes the birthplaces of the ancient poet Virgil and his own, showing the significance of cultural translation, with its logic of de- and refamiliarisation, for re-envisaging one’s poetic identity through the unexpected lens of otherness. As Heaney says, “the Irish home ground can be reviewed in the light of certain European perspectives – classical, medieval, and modern. These planes of regard allow us to get a closer view of that ground by standing back from it and help to establish a different focus, a more revealing angle of vision” (2012, 19). “From Mossbawn via Mantua” could, indeed, be seen, as an apology of translation, which can activate the imagination by ferrying the poetic self into the “home grounds” of others, or into a multiplicity of linguistic homelands other than his own. The “shortest route from self to self is through the other”, as Richard Kearney shows, pointing out the ontological dimension of translation, which refers to how one conveys one’s identity to others or, to come closer to Heaney’s sense, to how one comes to understand one’s identity via others (2004, xii-xv). In Heaney’s case, one route of passage from European to Irish destinations, one avenue of translation back to Mossbawn is that of a detour via the poetry of the Romanian Marin Sorescu, whom he locates in a so-called province of the Hyperboreans, “inhabited by different twentieth-century poets of Russia and Eastern Europe, poets who helped me make sense of my own situation in the turbulent Ireland of the 1970s and 80s” (2012, 21).